User Behavior in Public Transportation Mode Selection: A Systematic Literature Review - Nurhasanah, Rini; Fatimah, Ghaida Tsauraya Nur; Sugih, Ageng; Toruan, Erni Sari Lumban; Handayani, Susanty (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Urban mobility in Indonesia faces major challenges due to rapid urbanization, increasing private vehicle ownership, congestion, and pollution. In regions like West Java, including Bandung Raya and Majalengka, these issues are compounded by user preferences driven by comfort, cost, and travel time, often favoring private vehicles. As a developing country, Indonesia also struggles with weak inter-agency coordination, low infrastructure investment, and public stigma toward public transportation. This study employs the Systematic Literature Review (SLR) method to collect, analyze, and synthesize findings from existing research on transportation modes. Data were sourced using the Publish or Perish (PoP) software, which conducts targeted searches on Google Scholar—chosen for its accessibility and diverse sources compared to databases like Scopus or Web of Science. A total of 1,000 publications from 2000 to 2025 were analyzed. Using VOSviewer, the study examined keyword correlations and trends in publication themes over time. The results indicate a notable rise in transportation mode research since 2010, peaking around 2020. Overlay Visualization from VOSviewer reveals the temporal progression of key terms, highlighting growing interdisciplinary interest in public transportation issues. These findings provide valuable insight into the academic development of transportation studies and support policy discussions on sustainable urban mobility in Indonesia.